2020
DOI: 10.18231/j.ijpo.2020.078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of p53 in breast cancer and its correlation with various histological prognostic factors

Abstract: Carcinoma of the breast is the most common non-skin malignancy in women. The p53 gene is one of the most commonly mutated genes described in human neoplasia. Mutant p53 protein has greater stability and longer half time than the wild type protein that can be detected by Immunohistochemistry. This study was conducted to evaluate the expression of p53 in breast carcinoma and its correlation with various histological prognostic markers to determine its significance as a prognostic marker in breast cancer. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…In this study,out of 103 cases, 96 cases (93.2%) were of IDC-NOS type, 4 cases (3.9%) were of mucinous type, 2 cases (1.9%) were of Invasive lobular type, 1 case (1.0%) was of carcinosarcoma histological type. This was in concordance with observations of Patnayak et al [6] , Gupta et al (86.1%) [9] , Arora et al (84.6%) [1] and Sheikpour et al (84.6%) [12] . Which had IDC-NOS as the most common histological type.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In this study,out of 103 cases, 96 cases (93.2%) were of IDC-NOS type, 4 cases (3.9%) were of mucinous type, 2 cases (1.9%) were of Invasive lobular type, 1 case (1.0%) was of carcinosarcoma histological type. This was in concordance with observations of Patnayak et al [6] , Gupta et al (86.1%) [9] , Arora et al (84.6%) [1] and Sheikpour et al (84.6%) [12] . Which had IDC-NOS as the most common histological type.…”
Section: Resultssupporting
confidence: 92%
“…In maximum number of cases, size varied from 2-5cm (74.8% cases) followed by 16 cases (15.5%) with >5cm size and 10 cases with <2cm (9.7%) size. This is in concurrence with the results obtained by Patnayak et al [6] , Piplani et al [7] , Gupta et al [19] , Arora et al [1] and Neharika et al [10] who found 79.6%, 67.7%, 63.9% and 59.6% and 53.9%. Another Study conducted by Prabhu et al showed maximum number of cases with tumour size between 2-5 cm in size [11] .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations